Expanding (Environmental) Histories of the Holocaust. Issue 2 (2nd April 2020) - Cole, Tim
ABSTRACT: This epilogue draws out three ways that environmental histories of the Holocaust might challenge the current historiography to expand its horizons. Firstly, environmental histories of the Holocaust expand the range and nature of actors studied as we seek to understand genocide and its aftermath. Secondly, and closely linked to this, environmental histories of the Holocaust expand the range and nature of sources and methods drawn upon in genocide research. Thirdly, environmental – and ecological – histories of the Holocaust expand the chronological boundaries of study when conceptualizing histories of genocide. Taken together, the nascent literature on environmental and ecological histories of the Holocaust offer an important extension of what writing "integrated" histories of the Holocaust might entail.